Pengaruh Teknik Kontrak Perilaku terhadap Perilaku Menyontek Siswa di SMP Negeri 1 Luhak Nan Duo Kabupaten Pasaman Barat - Rahmadayani, Putri; Yusri, Fadhilla (YASIN, 2023)
Cheating behavior is any act or trick that is dishonest, dishonest behavior and cheating carried out by someone to achieve success. This research was motivated by the existence of several students who were indicated to have cheated during exams or learning evaluations. The aim of the research is to determine the effect of behavioral contracts in individual counseling to overcome students' cheating behavior at SMPN 1 Luhak Nan Duo, West Pasaman Regency. This research is classified as Pre-Experimental research using the One Group Pretest Posttest Design model. The population was 38 students in class VIII at SMPN 1 Luhak Nan Duo, West Pasaman Regency, while the research sample was students who were indicated to have cheated, taken based on purposive sampling techniques and pretest results, totaling 5 people. The data collection instrument is a Likert scale. Data analysis techniques for non-parametric statistical tests, the Wilcoxon signed rank test method, with the help of (SPSS) version 24.00. From the calculation of the scale score results, the results of students' cheating behavior before treatment (pretest) obtained a mean of 79.00, this is classified as medium criteria. Meanwhile, after treatment (posttest), the mean was 65.80, which is classified as low criteria. The calculation results show the difference between the pretest score and the posttest score. This statement is based on a Zcount value of 2.023, while a Ztable with a degree of freedom (df) of 4 is obtained at 1.96 at a significance level of 0.05. So it can be seen that the value of Zcount> Ztabel is 2.023 > 1.96, so there is a difference in the average test score between before treatment was given to students who committed acts of cheating and after treatment was given to students who committed acts of cheating so that Ho was rejected and H1 was accepted.